Pengembangan Media Pembelajaran Komik Digital Dilengkapi Video Faktual sebagai Media Pembelajaran Mata Kuliah Kultur Jaringan - Fadilah Ismail; Diky Setya Diningrat (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research was motivated by the lack of alternative technology-based learning media other than Powerpoint in the tissue culture lecture process and the difficulty of biology education students in understanding technique-based tissue culture material due to the absence of a tissue culture laboratory. Given these problems, researchers developed digital comic learning media equipped with factual videos to help students understand the material well. This research aims to (1) produce appropriate and effective learning media based on digital comics based on the assessment of material experts. (2) produce appropriate and effective learning media based on digital comics based on the assessment of media experts. (3) produce appropriate and effective learning media based on digital comics based on student responses to the tissue culture course, material on tissue culture techniques in callus culture. The development model used is the ADDIE model with research subjects of 26 biology education students. The development of digital comic learning media equipped with factual videos has met the validity and effectiveness criteria with the conclusion that the learning media is very good to use based on the results of the material expert validity questionnaire with a score of 90% and the media 83.16%. The effectiveness results obtained from the student questionnaire were 91.21% in small group trials.